2006
DOI: 10.1128/aem.72.3.1858-1872.2006
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Dynamics of Bacterial Communities of a Drinking Water Supply System as Assessed by RNA- and DNA-Based 16S rRNA Gene Fingerprinting

Abstract: Bacterial community dynamics of a whole drinking water supply system (DWSS) were studied from source to tap. Raw water for this DWSS is provided by two reservoirs with different water characteristics in the Harz mountains of Northern Germany. Samples were taken after different steps of treatment of raw water (i.e., flocculation, sand filtration, and chlorination) and at different points along the supply system to the tap. RNA and DNA were extracted from the sampled water. The 16S rRNA or its genes were partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
177
4
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(207 citation statements)
references
References 44 publications
22
177
4
4
Order By: Relevance
“…Bacterial community change through the drinking water treatment units has still been poorly characterized. Eichler et al (2006) found that no major changes of bacterial community structures occurred after flocculation and sand filtration. In contrast, Pinto et al (2012) found that filtration by dual media rapid sand filters could shape the bacterial community in waters.…”
Section: Bacterial Community Structuresmentioning
confidence: 95%
See 3 more Smart Citations
“…Bacterial community change through the drinking water treatment units has still been poorly characterized. Eichler et al (2006) found that no major changes of bacterial community structures occurred after flocculation and sand filtration. In contrast, Pinto et al (2012) found that filtration by dual media rapid sand filters could shape the bacterial community in waters.…”
Section: Bacterial Community Structuresmentioning
confidence: 95%
“…Since the presence of certain bacteria may lead to water quality problems in the downstream DWDS, knowledge of the bacterial ecology in the effluents of drinking water treatment units will be of practical importance. Unfortunately, only very few works have investigated the microbial communities in the effluents of drinking water treatment units (Eichler et al 2006;Poitelon et al 2010). Therefore, the bacterial community in the effluents of drinking water filters remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is expected that in drinking water, both the diversity of bacterial species and the possible occurrence of antibiotic resistance will have different characteristics of what can be found in wastewater. Water disinfection is known to cause a dramatic bottleneck on bacterial diversity (Hoefel et al 2005;Eichler et al 2006;Vaz-Moreira et al 2013) and bacteria ubiquitous in aquatic environments, such as members of the genus Aeromonas, may be reduced to levels below the limit of detection by culture-dependent methods (Figueira et al 2011). However, other groups that comprise bacteria with recognized ubiquity and genome plasticity, demonstrated by the acquired capacity to degrade xenobiotics or to resist to some antibiotics, such as members of the genera Pseudomonas, Acinetobacter, or family Sphingomonadaceae, are commonly found in tap water (Vaz-Moreira et al 2014).…”
Section: Drinking Watermentioning
confidence: 99%